2022
DOI: 10.1080/13880209.2022.2134898
|View full text |Cite
|
Sign up to set email alerts
|

Qushi Huayu decoction attenuated hepatic lipid accumulation via JAK2/STAT3/CPT-1A-related fatty acid β-oxidation in mice with non-alcoholic steatohepatitis

Abstract: Context Qushi Huayu decoction (QHD) has been clinically used for treating non-alcoholic steatohepatits (NASH). However, little is known about the effect of QHD on fatty acid β-oxidation (FAO)-dependent lipid consumption. Objective To investigate the mechanism of QHD on FAO-related hepatic lipid accumulation. Materials and methods Male C57BL/6J mice were randomly divided into 5 groups ( n = 8): normal diet and drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Inhibition of Notch signaling can regulate lipid metabolism and improve nonalcoholic fatty liver disease. The pro-fibrotic effect of Notch signaling is related to impaired lipid metabolism of renal tubular epithelial cells [ 24 ], and regulation of stat3 signaling can promote the oxidation of fatty acids and improve lipid accumulation in liver [ 27 ]. In this study, we hypothesized that CA could inhibit Notch1 and stat3 signaling, and that CA might regulate Notch1 and stat3 signaling to inhibit renal lipid accumulation and renal fibrosis induced by high glucose and high lipid in HK2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of Notch signaling can regulate lipid metabolism and improve nonalcoholic fatty liver disease. The pro-fibrotic effect of Notch signaling is related to impaired lipid metabolism of renal tubular epithelial cells [ 24 ], and regulation of stat3 signaling can promote the oxidation of fatty acids and improve lipid accumulation in liver [ 27 ]. In this study, we hypothesized that CA could inhibit Notch1 and stat3 signaling, and that CA might regulate Notch1 and stat3 signaling to inhibit renal lipid accumulation and renal fibrosis induced by high glucose and high lipid in HK2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that inhibiting stat3 activation in STZ-induced DKD can prevent the progression of fibrosis [ 26 ] and inhibited Stat3 signal can promote fatty acid oxidation and thus improve lipid accumulation in the liver. [ 27 ]. Moreover, cross-talk between Notch-Hes and stat3 signaling has also been reported [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…QHD has been clinically used for NAFLD treatment in China for decades. In recent studies, the mechanism of QHD in NAFLD is related to the biological functions of reducing oxidative stress, regulating intestinal microbiota, regulating body metabolism and signaling pathways, promoting browning of white adipose tissue, and inhibiting lipogenesis ( 9 , 12 , 14 , 15 , 34 , 35 ). Furthermore, it has been reported that many bioactive components of QHD have significant anti-NAFLD activities.…”
Section: Discussionmentioning
confidence: 99%
“…As a clinical empirical prescription, Qushi Huayu decoction (QHD) has been used in the intervention of NAFLD in China for several decades ( 9 , 10 ). The efficacy of QHD has been demonstrated in several models of NAFLD in vivo and in vitro ( 9 , 11 13 ), and the mechanisms include regulation of branched-chain amino acid metabolism disorder, upregulation of AMPK/SIRT1/UCP-1 signaling pathway ( 14 ), modulation of fatty acid β-oxidation ( 15 ), regulation of gut microbiota composition, and protection of intestinal tight junctions ( 16 ).…”
Section: Introductionmentioning
confidence: 99%